2010
DOI: 10.1177/0265532209360671
|View full text |Cite
|
Sign up to set email alerts
|

Judgments of oral proficiency by non-native and native English speaking teacher raters: Competing or complementary constructs?

Abstract: This paper reports the findings of an empirical study on ESL/EFL teachers' evaluation and interpretation of oral English proficiency as elicited by the national College English Test-Spoken English Test (CET-SET) of China. Informed by debates on the issue of native speaker (NS) norms which have become the focus of attention in recent years, this study addresses the question of whether judgments of language proficiency by non-native English speaking (NNES) teachers, who are currently used to assess performance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(29 citation statements)
references
References 55 publications
2
20
0
Order By: Relevance
“…However, the NS-NNS dichotomy has been questioned by World Englishes scholars (e.g., Davies, 1999). Furthermore, previous studies have found that raters' scores did not always reflect how raters interpreted and applied the scoring rubrics (e.g., Zhang & Elder, 2011). To address these concerns, this study used Kachru's framework of three concentric circles (1982,1985) to categorize rater types and a mixed-method design to investigate the qualitative differences in scoring processes and the quantitative differences in scores.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the NS-NNS dichotomy has been questioned by World Englishes scholars (e.g., Davies, 1999). Furthermore, previous studies have found that raters' scores did not always reflect how raters interpreted and applied the scoring rubrics (e.g., Zhang & Elder, 2011). To address these concerns, this study used Kachru's framework of three concentric circles (1982,1985) to categorize rater types and a mixed-method design to investigate the qualitative differences in scoring processes and the quantitative differences in scores.…”
Section: Introductionmentioning
confidence: 99%
“…Kim (2009) compared the differences in Korean English teachers and Canadian English teachers in judging Korean English learners' oral proficiency. Zhang and Elder (2011) compared Chinese native speakers and English native speakers' ratings of Chinese students' oral proficiency in the national College English Test-Spoken English Test (CET-SET) in China. More recently, however, researchers have become more interested in speakers of English varieties from Outer Circle countries such as India (Carey et al, 2011;Hsu, 2012;Xi & Mollaun, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Zhang and Elder (2011) in their study report that native and non-native English speaking teachers weigh various features of oral proficiency in making their decisions on Input source and EFL learners' perceptions towards it, on their listening performances, across gender…”
Section: Introductionmentioning
confidence: 99%